The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics–including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty–for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis